Incidence and risk factors of injuries in Brazilian elite handball players: A prospective cohort study - Giroto, N.; Hespanhol Junior, L. C.; Gomes, M. R. C.; Lopes, A. D. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The aim of this study was to investigate the incidence and risk factors for handball injuries in Brazilian elite handball players. Overall, 339 athletes from 21 handball teams who participated in the two main Brazilian championships were followed up during a season. In total, 312 injuries were reported by 201 athletes. The injury incidence rate during training was 3.7/1000 h, and during matches was 20.3/1000 matches. Ankle (19.4%, n = 46) and knee (13.5%, n = 32) were the body regions most affected by traumatic injuries. Shoulders (44.0%, n = 33) and knee (26.7%, n = 20) were the body regions most affected by overuse injuries. Muscle injuries (27.1%, n = 68) was the traumatic injury type most reported. Tendinopathy (91.8%, n = 56) was the overuse injury type most observed. Previous injury (OR: 2.42, CI 95%: 1.51-3.89) and an additional match per week (OR: 1.31, CI 95%: 1.05-1.62) were associated with a higher risk of overuse injury. Female athletes (OR: 1.56, CI 95%: 1.08-2.25) and an additional hour of training per week (OR: 1.09, CI 95%: 1.02-1.15) were associated with a higher risk of traumatic injury. This study showed that athletes with previous injury have shown a high risk of developing an overuse injury.